Kajian semula pengurusan kokurikulum sekolah menengah kebangsaan - Shahadan, Sulaiman (2008)
Restudy on School Co-curriculum Management System was a study conducted on Pekan Nanas Secondary School co-curriculum management. Result from the study shows that the current co-curriculum management is not conducted smoothly and systematically. Therefore, a system that is able to help the co-curriculum management in the school is developed. Before it was developed, all the information regarding the work process on co-curriculum management in the school were gathered. Also, the researcher has proposed a new work process after analyzing the current work process based on the Business Process Improvement study (BPI) technique. In reference to the BPI process the researcher then developed a system called ekoQ System. The researcher used UML (Unified Modeling Language) Model and Prototype Model to analyze and developed the system on web environment. ekoQ System can help the administrator and co-curriculum managers to handle and manage the school co-curriculum management electronically. This system can also extract the required data from the Student Information System (SMM) that currently used in the school. Student co-curriculum marks also can be generated automatically in order to leverage the teacher advisor burden. Another feature is, this system is also able to produce student electronic portfolio